Characterization of negative bias temperature instability in ultra-thin oxynitride gate P-MOSFETs - Wang, Shuang (2009)
Negative Bias Temperature Instability (NBTI) is a critical reliability issue of metal-oxide-semiconductor field effect transistors (MOSFETs) due to imperfections located at the oxide-semiconductor interface. According to the conventional NBTI model, interface traps are generated at the Si-SiO2 interface, due to the dissociation of Si-H bonds during NBTI stressing. Interface traps were believed to be the only interfacial imperfections that cause NBTI-induced degradation. In this thesis, however, it is found that deep-level oxide charges with distinct physical origins from interface traps play a significant role in the NBTI problem. These deep-level trapped charges are located in the oxide near the Si-SiO2 interface, but of high energy states beyond the electron tunneling energy window and the charge pumping current measurement capability. Therefore, they contribute to an important portion of threshold voltage shift during NBTI stressing, and remain charged after the stress is terminated. Furthermore, deep-level oxide charge is related to nitrogen in the gate oxide. More nitrogen enhances the generation of deep-level hole traps and results in severer threshold voltage shift. Besides, activation energy of NBTI-induced degradation was extracted to study NBTI mechanisms. Contrary to the single activation energy of the conventional SiO2 gate p-MOSFET, two distinct activation energies were obtained on ultra-thin oxynitride gate p-MOSFETs. One of the activation energy coincides with that obtained from the R-D model on SiO2 gate p-MOSFET; while the other activation energy is much smaller, representing a thermally-insensitive mechanism. Compared to the R-D mechanism, the thermally-insensitive mechanism is less dependent on temperature and stress time, but more sensitive to nitrogen in the gate oxide. With more nitrogen in the gate oxide, degradation due to the thermally-insensitive mechanism is significantly increased. This novel nitrogen-related thermally-insensitive NBTI mechanism superposes on the R-D mechanism, leading to severer degradation of nano-scale oxynitride p-MOSFETs.